PENERAPAN ALGORITMA FLOYD WARSHALL PADA SISTEM INFORMASI GEOGRAFIS LOKASI PARIWISATA KOTA PADANG SIDEMPUAN BERBASIS ANDROID - Nazrah Namira Siregar; Suendri Suendri; Triase Triase (UIN Sumatera Utara Medan, 2021)
Geographic Information System is a system created based on the geographic mapping of the earth. This system can provide information about the location of the area or the location of places on the earth's surface, provide information about a location and information about the shortest path from one location to another. The city of Padang Sidempuan currently has many tourist attractions that have a beauty that is not far from other cities, such as Tor Simarsayang, Silima-Lima Waterfall, Aek Sabaon and others. However, currently there is no application that can make it easier for tourists to get information to get to the tourist attractions in question. The Floyd-Warshall algorithm is a method that performs problem solving by looking at the solution that will be obtained as an interrelated decision and will choose the shortest path from several alternative paths that have been generated from the calculation process. In this study using the waterfall research method, android programming language and MySQL database with data as much as 10 tourism points. The final results were tested using the black box testing method, obtained an average accuracy of 90% of the results of the shortest distance from each point and the system can display features, such as tourist data features, tourist facilities, cost estimates, tourist pictures and opening times of the tourist attractions